Study on the Load-Bearing and Mechanical Properties of Coal Specimens Under Uniaxial Compression with Polyurea Spraying - Shuwen Cao; Jinhong Yang; Dingyi Hao (Applied Sciences)
Polyurea spraying is a new temporary support technology that can significantly enhance the mechanical properties of coal. However, the mechanism of interactions between the polymer coating and coal is unclear. In this study, the No. 4 non-stick coal from Mengcun Coal Mine and polyurea material were used to conduct experiments and numerical simulations. The tests and simulations were used to examine the role of the sprayed coating in the formation of residual strength and the unloading and rebound mechanism after brittle failure of the coal. The results showed that the presence of the polyurea coating had a significant impact on the mechanical behavior of the coal. The specimens sprayed with polyurea were affected by the confining pressure applied by the coating and the internal friction of the coal; consequently, the specimens exhibited certain plastic characteristics and maintained their residual strength after experiencing brittle failure. The polyurea coating not only effectively prevents the loosening and slippage of the coal but also improves the stability of the coal by altering its mechanical behavior during the loading process. This study lays the foundation for popularizing and applying polyurea spraying technology in coal mine support while providing rich data to support further theoretical research.